Intersecções entre psicanálise, política e a clínica do autismo - Moraes, Natália de Andrade de (2017)
This research aimed to problematize the psychoanalysis-politics relationships, in connection with psychoanalysis practices on autism. Therefore, there were conducted two studies. The first one is a systematic literature review, centered in the following question: How, or through which operators, might be produced a rigorous articulation between the politics and psychoanalysis fields? The results, narratively presented, composed a complex conceptual table that embraces reflections on politics, social and power as constitutive parts of the history of psychoanalysis, definitely marked by the political field. The second study aimed to problematize the autism statute in the contemporary, as well as the place defined to autistic subjects in a social crossed by neoliberal and capitalist speeches. Thus, it was proposed the analysis of an advertisement video referring to the “the hug jacket”, a product destined to calm down autistic children. In an ultra-individualist scenario, objects‟ imperative and lacking social bonds, the autistic subject emerges in the place of weirdness when reflecting on the contemporary tendency of the Other‟s absence, the monotony and the isolation. In such context, the psychoanalysis proposes a possible way out to the capitalist speech throughout the introduction of the innovative, in the support of a desire that enables the subject its tiny singularity that it owns. Finally, the research reflected on the important psychoanalysis function, which is political, as a speech that enables the alterity registration and the rescue of difference, desire and the sovereignty of the Other. As for the psychoanalysis practices on autism, this function is expressed by the non-withdrawal of psychoanalysts in promoting with the subjects an encounter to what is possible, that pull them out of the helplessness condition to which they are exposed by normative strategies.